Cote d'Ivoire-Assessment Letter for the International Financial Community. (Policy Papers; Policy Paper ;, 2010)
This paper sets forth a proposal for an expanded and more flexible NAB. The proposal was developed in close consultation with current and potential participants in the NAB, including through meetings of current and potential participants in April, July, and November 2009 in Washington, D.C. under the chairmanship of Japan.